EXPERIMENTAL STUDY OF CADMIUM INDUCED HEPATIC TOXICITY - Masud, Khawaja Usman; Nagi, A. H. (Journal of Ayub Medical College Abbottabad, 2000)
Background: Cadmium is a modern toxic metal. It is a proven environmental pollutant and has hepatotoxic effects as well. This study was carried out to look for hepatotoxicity of cadmium in rabbits. Methods: Forty rabbits divided into four equal groups (3 experimental and 1 control) were used. Minimum Lethal dose and experimental dose of Cadmium Sulphate were calculated. Group I was injected with half minimal lethal dose, Group II with experimental dose and Group III with 30% specific bovine albumin, followed by experimental dose. The control group was injected with distilled water. This treatment was continued for 12 weeks. During the experiment serum alanine transferase (S-ALT) and gamma glutamide transpeptidase (y-GT) were estimated twice, at intervals of 6 weeks and 12 weeks followed by autopsy at the end of the experiment. The liver was excised after sacrificing the animals. The tissue was processed for histopathology. Results: A definite rise in the enzymes and changes in normal liver histology were observed. Conclusions: The cadmium induced lesions in the liver appear to be dose and time dependent. The findings of this study suggest that cadmium has direct toxic effects on liver leading to hepatic damage. It is therefore recommended that the environmental cadmium pollution and uncontrolled industrial use of this metal must be controlled.